The Effect of Differentiated Learning on Improving Student Learning Outcomes - Aguanda; Setiawan, Agus; Anwar, M. Saidun; Wardana , Muhammad Rafli Faishal; Yambasu, Rebecca Alicia (CV. Bimbimbingan Belajar Assyfa, 2023)
This research aims to obtain objective information and examine differences in the abilities of reasoning mathematical students who study with method learning differentiate assistance with RME-based matrix teaching materials from students who use conventional methods. This research uses a quantitative approach with experimental research methods pseudo (quasi-experiment) with type non-equivalent control groups design. The study was carried out in the even semester of the 2022/2023 academic year in the mathematics subject matrix material. The subjects in the research involved students of class XI APHP at SMK Negeri 2 Metro Lampung consisting of class XI APHP 1 as the experimental class and XI APHP 2 as the control class. In the study, the data collected used test beginning (pretest) and the final (posttest) given to the experimental style, and the control class consisted of 4 essay questions. The statistical data obtained were normality, homogeneity, and hypothesis tests, which were processed using the SPSS 16.0 program. Based on the results of the hypothesis test, a significance value (2- 2-tailed) was obtained of 0.000. Therefore, the significance value was <0.05, so it can be concluded that the results of this research show that there is an influence of differentiated learning assisted by RME-based matrix teaching materials on mathematical reasoning abilities. class XI APHP student at SMK Negeri 2 Metro Lampung.